2011
DOI: 10.1007/s10389-011-0446-y
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and perception of complementary and alternative medicine use by patients in western Nepal

Abstract: Aim This study aims to investigate the patterns of complementary and alternative medicine (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 19 publications
5
19
0
Order By: Relevance
“…[18] The use of CAM is more common among patients with chronic conditions for which patients had already tried allopathic medicine. [21] In the present study also the most common ailments for which CAM practiced was arthritis, chronic pain, diabetes mellitus, gastrointestinal conditions and HIV. The reason for this might be only symptomatic relief and lack of complete cure produced by conventional medicines for these conditions.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…[18] The use of CAM is more common among patients with chronic conditions for which patients had already tried allopathic medicine. [21] In the present study also the most common ailments for which CAM practiced was arthritis, chronic pain, diabetes mellitus, gastrointestinal conditions and HIV. The reason for this might be only symptomatic relief and lack of complete cure produced by conventional medicines for these conditions.…”
Section: Discussionsupporting
confidence: 50%
“…Similarly in the study from Nepal Ayurveda and yoga were common modalities of CAM use. [21] Homeopathy is frequently utilized alternate system of medicine in Far East countries, Pakistan and UAE. [3] The system of the CAM selected depends on the accessibility and affordability, the profi le of the disease states, awareness, past experience and beliefs about CAM and their social acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Nepal reported that patients with a higher education level, higher income, and age above 40 years were found more likely to use CAM. 21 Some CAM studies in arthritis reported majority of CAM users in age group of less than 57 years. 16 In contrast in our study majority (77%) of CAM users were above 60 years of age group.…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of the world population has already adopted 'back to the nature' strategy to maintain a healthier life and still there is an increasing trend of using natural medicine based in complementary and alternative therapies in developed as well as developing countries (Dhami, 2008;Eisenberg et al, 1998;Ernst and White, 2000;Faurtel et al, 2002;Kadayat et al, 2012;Sen et al, 2011). It is estimated that about 300,000 plant species are found worldwide and about 10% of them are considered as medicinally important (Evans, 1996).…”
Section: Prospects Of Pharmacognosy Research and Educationmentioning
confidence: 99%